2008
DOI: 10.1111/j.1440-1827.2008.02232.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant MAD2 expression in soft‐tissue sarcoma

Abstract: Soft-tissue sarcomas can be divided into translocationassociated (TA) and non-TA sarcomas, the latter of which is often characterized by pleomorphic cytomorphology and aneuploidy. The aberrant expression of MAD2, an essential component of the mitotic spindle checkpoint, has been recently shown to promote aneuploidy. The aim of the present paper was to assess MAD2 status on immunohistochemistry in 50 TA sarcomas with known fusion genes and 50 non-TA pleomorphic sarcomas. MAD2 was overexpressed in 26 TA (52%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…Our previous study demonstrated that Mad2 was overexpressed in human osteosarcoma tissue, and that increased expression of Mad2 was associated with early metastasis and poor survival (10). The findings of several reports are in accordance with our studies in many different malignant tumors (8,(11)(12)(13). The exact relationship between Mad2 expression and clinical outcome remains unclear.…”
Section: Introductionsupporting
confidence: 82%
“…Our previous study demonstrated that Mad2 was overexpressed in human osteosarcoma tissue, and that increased expression of Mad2 was associated with early metastasis and poor survival (10). The findings of several reports are in accordance with our studies in many different malignant tumors (8,(11)(12)(13). The exact relationship between Mad2 expression and clinical outcome remains unclear.…”
Section: Introductionsupporting
confidence: 82%
“…The downregulation of MAD2 is responsible for mitotic checkpoint abrogation and chromosomal instability in human cancers [11][12][13][14][15]. Wang et al [34] reported that MAD2-induced sensitisation to VCR is associated with Raf/Bcl-2 phosphorylation and mitotic arrest in nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…missegregation and mitotic catastrophes [2][3][4][5]. The mutation of the Mad2 gene is very rare in many kinds of human cancer [6][7][8][9], but deletion or downregulation of MAD2 has also been reported in several human cancers such as lung cancer [10], breast cancer [11], nasopharyngeal cancer [12], soft-tissue sarcoma [13,14], and ovarian carcinoma [15].…”
Section: Introductionmentioning
confidence: 99%
“…Immunostaining was scored as the ratio of the number of strongly stained nuclei to the total number of cells as described in our previous article [17]. Less than 10% staining of tumor nuclei was designated as representing a low level of MAD2 expression, and more than 10% staining was considered a high level of MAD2 expression [18]. The Ki-67 labeling index was calculated as a percentage of immunopositive cells.…”
Section: Tissue Microarrays and Immunohistochemistrymentioning
confidence: 99%